Yunxiangalkali silane, preparation method thereof and metasilicate composite powder
By modifying metasilicate composite powder by vanillin silane, the compatibility problem of natural mineral powder when bonding with polyolefin substrates is solved, higher dispersion and functionality are achieved, and its application scope is expanded.
Patent Information
- Application Number
- CN202510046019.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-11
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-11
AI Technical Summary
The existing natural mineral powders have compatibility problems when combined with low-polar polyolefin elastomer substrates. The modification effect of traditional silane coupling agents is limited, making it difficult to meet the wider application needs.
The metasilicate composite powder is modified by one-step replacement reaction, reducing its surface polarity and improving dispersion and functionality.
It effectively reduces the oil absorption value of natural mineral powder, improves its dispersion and functionality in polyolefin matrix, expands its application scope, and significantly improves the mechanical properties and carbon-forming properties of composite materials.
Smart Images

Figure CN119823171A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional materials, and in particular to a kind of silane and a preparation method thereof, and a metasilicate composite powder. Background Art
[0002] The rational development and application of natural mineral powders can effectively alleviate the problems of fossil energy depletion and high carbon consumption. The adoption of multifunctional design concepts can significantly enhance the application value and potential of these natural mineral powders. In addition, the simple and efficient preparation process not only saves time and cost, but also supports large-scale production and utilization in diversified application scenarios.
[0003] However, most natural mineral powders face compatibility issues when combined with low-polarity polyolefin elastomer substrates due to their strong surface polarity and rich hydroxyl groups. Traditionally, silanes are often used to modify the surface of natural mineral powders, but this method often cannot meet the needs of a wider range of applications. For example, calcium metasilicate, as a mineral commonly found in nature, has excellent physical filling properties, but there are still many limiting factors in practical applications. For example, calcium metasilicate prepared by physical methods has problems such as high surface polarity, easy agglomeration, poor processing performance, and easy precipitation. Traditional silane coupling agents can improve these problems to a certain extent, but their functionality is still limited.
[0004] Therefore, there is an urgent need to provide a modified material that can greatly improve the functionality of natural mineral powders. Summary of the invention
[0005] In view of this, the present invention provides a silane and a preparation method thereof and a metasilicate composite powder to solve the problem of poor functionality of the existing traditional silane coupling agent modified natural mineral powder.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The present invention provides a silane, the structural formula of which is shown in Formula I:
[0008]
[0009] The present invention also provides a method for preparing silane, comprising the following steps:
[0010] 1) mixing the safflower oil solution with the alcohol solution of the inorganic salt to obtain a first solution;
[0011] 2) mixing the first solution with the aromatic bromosilane solution to carry out a substitution reaction to obtain aromatic silane;
[0012] The structural formula of the caryophyllene in the caryophyllene solution is shown in Formula II:
[0013]
[0014] The structural formula of the aromatic bromosilane in the aromatic bromosilane solution is shown in Formula III:
[0015]
[0016] Preferably, in step 1), the molar ratio of carmine in the carmine solution to the inorganic salt in the alcohol solution of inorganic salt is 1:1-5; the concentration of the carmine solution is 1-3 mol / L; the concentration of the alcohol solution of inorganic salt is 1-5 mol / L.
[0017] Preferably, the mixing in step 1) is to drop the safflower oil solution into the alcohol solution of the inorganic salt, and the dropping rate is 5 mL / s to 1 mL / s.
[0018] Preferably, the molar ratio of the aromatic bromosilane in the aromatic bromosilane solution to the carmine in the carmine solution in step 2) is 1 to 3:1; and the concentration of the aromatic bromosilane solution is 1 to 3 mol / L.
[0019] Preferably, the mixing in step 2) is to drop the aromatic bromosilane solution into the first solution at a rate of 5 mL / s to 1 mL / s; the temperature of the substitution reaction in step 2) is 55 to 100°C, the heating rate is 5 to 20°C / h, and the time is 1 to 24h.
[0020] Preferably, the inorganic salt in the alcohol solution of the inorganic salt includes one or more of sodium carbonate, cesium carbonate, sodium bicarbonate, potassium carbonate, calcium carbonate, magnesium hydroxide and aluminum hydroxide; the alcohol in the alcohol solution of the inorganic salt includes one or more of ethanol, methanol, n-butanol, ethylene glycol, neopentyl alcohol, isopropanol and propanol; the solvent in the rosin solution and the solvent in the aromatic bromosilane solution independently include one or more of water, N,N-dimethylformamide, ethyl acetate, tetrahydrofuran, dimethyl sulfoxide, methanol, ethanol and propanol.
[0021] The present invention also provides a method for preparing a metasilicate composite powder, comprising the following steps:
[0022] S1: mixing the silane described in claim 1 with an organic solvent to obtain a second solution;
[0023] S2: mixing the second solution with the metasilicate slurry, reacting them to obtain a metasilicate composite powder.
[0024] Preferably, the concentration of the second solution in S1 is 1 to 5 mol / L; the mixing temperature in S1 is 25 to 50° C., and the mixing time is 10 to 180 min.
[0025] Preferably, the mass molar ratio of metasilicate to silane in the metasilicate slurry in S2 is 1-20 kg:1 mol; and the concentration of the metasilicate slurry is 1-5 kg / L.
[0026] Preferably, the mixing in S2 is spraying the second solution into the metasilicate slurry, the rate of spraying the second solution into the metasilicate slurry is 1-30 mL / min, and the temperature is 25-45°C; the temperature of the reaction in S2 is 50-95°C, the heating rate is 5-30°C / h, and the time is 0.2-6.0h.
[0027] Preferably, the organic solvent comprises one or more of N,N-dimethylformamide, ethyl acetate, dimethyl sulfoxide and tetrahydrofuran; the median particle size D of the metasilicate in the metasilicate slurry is 50 The particle size is 1.0 to 4.0 μm; the dispersion in the metasilicate slurry includes one or more of methanol, ethylene glycol, ethanol, propanol, n-butanol, isopropanol, neopentyl alcohol, and isopropanol; and the metasilicate includes natural calcium metasilicate.
[0028] The present invention also provides a metasilicate composite powder prepared by the above-mentioned metasilicate composite powder preparation method.
[0029] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The present invention adopts the natural product bromobiprofen and aromatic bromosilane to obtain bromobiprofen silane (BMPMMP) through a one-step substitution reaction. The bromobiprofen silane (BMPMMP) is a nitrogen-macroconjugated silane compound. The macroconjugated nitrogen borate in the metasilicate composite powder modified by the nitrogen-macroconjugated silane compound contains a polycyclic conjugated aromatic ring structure and has low surface energy. It can effectively shield the hydroxyl groups on the surface of the natural calcareous metasilicate mineral powder, reduce its surface polarity, and reduce the oil absorption value of the natural mineral powder. At the same time, bromobiprofen silane is a low-polarity natural product post-modification product. After modifying the natural metasilicate, it can not only greatly save the processing cost, but also effectively improve the dispersibility of the obtained metasilicate composite powder in the polyolefin matrix, which has a good promoting effect on the high value and functional improvement of the natural mineral powder. The overall preparation process can be prepared by a one-step method, which is suitable for large-scale industrial production.
[0031] 2. The metasilicate composite powder (BMPMMP-NMS) of the present invention is a white artificial functional natural inorganic composite powder with a core-shell structure, and is also a reconstructed product of a variety of natural products (meat lysine and natural calcium silicate). The BMPMMP-NMS has excellent chemical stability, low oil absorption value, high dispersibility, good carbonization and enhanced toughness, and can be added to the polymer matrix as a multifunctional composite filler to play the role of filling, strengthening, toughening, and promoting carbonization. It can effectively expand the application scope of natural mineral powders, enable them to play a role in more fields, and show greater value.
[0032] 3. The core-shell structure of the BMPMMP-NMS described in the present invention contains N and Si elements on the outside, which can improve the flame retardant effect. The large conjugated aromatic ring on its surface can effectively form carbon during the combustion process. The natural calcium metasilicate inside its core-shell structure has strong stability and a certain aspect ratio, which can effectively improve the tear resistance and tensile strength of the composite material. During the combustion process, a large amount of carbonized products can be attached to the internal calcium metasilicate skeleton to form an enhanced carbon layer with excellent thermal stability and strong impact resistance, which is beneficial to strengthen the physical barrier effect. This internal and external synergistic effect can effectively improve the flame retardant, carbonization and smoke suppression properties of the BMPMMP-NMS material, greatly expanding the functionality of the BMPMMP-NMS material. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0034] Figure 1 Schematic diagram of the structure of the metasilicate composite powder (BMPMMP-NMS) prepared in Example 1.
[0035] Figure 2 This is the particle size distribution diagram of the metasilicate composite powder (BMPMMP-NMS) prepared in Example 1.
[0036] Figure 3 This is the SEM image of the metasilicate composite powder (BMPMMP-NMS) prepared in Example 1. DETAILED DESCRIPTION
[0037] The present invention provides a silane, the structural formula of which is shown in Formula I:
[0038]
[0039] The present invention also provides a method for preparing silane, comprising the following steps:
[0040] 1) mixing the safflower oil solution with the alcohol solution of the inorganic salt to obtain a first solution;
[0041] 2) mixing the first solution with the aromatic bromosilane solution to carry out a substitution reaction to obtain aromatic silane;
[0042] The structural formula of the caryophyllene in the caryophyllene solution is shown in Formula II:
[0043]
[0044] The structural formula of the aromatic bromosilane in the aromatic bromosilane solution is shown in Formula III:
[0045]
[0046] In the present invention, the molecular formula of the silane is C 24 H 28 N2O2Si, relative molecular mass is 404.19.
[0047] In the present invention, the alcohol solution of the inorganic salt in step 1) is a dispersion of the inorganic salt.
[0048] In the present invention, the molar ratio of the carmine in the carmine solution to the inorganic salt in the alcohol solution of the inorganic salt in step 1) is 1:1-5, preferably 1:2-4, and more preferably 1:3; the concentration of the carmine solution is 1-3 mol / L, preferably 2 mol / L; the concentration of the inorganic salt dispersion is 1-5 mol / L, preferably 2-4 mol / L, and more preferably 3 mol / L.
[0049] In the present invention, the mixing in step 1) is to drop the carmine solution into the alcohol solution of the inorganic salt, and the dropping rate is 5mL / s to 1mL / s, preferably 4mL / s to 2mL / s, and more preferably 3mL / s; the mixing temperature is preferably room temperature; the stirring speed of the mixing is preferably 100 to 1200rpm, more preferably 150 to 1000rpm, and more preferably 200 to 500rpm; the mixing time is preferably 1 to 18h, more preferably 5 to 15h, and more preferably 10 to 12h.
[0050] In the present invention, the molar ratio of the aromatic bromosilane in the aromatic bromosilane solution to the carmine in the carmine solution in step 2) is 1 to 3:1, preferably 2:1; the concentration of the aromatic bromosilane solution is 1 to 3 mol / L, preferably 2 mol / L.
[0051] In the present invention, the method for preparing the aromatic bromosilane solution in step 2) is preferably to dissolve the aromatic bromosilane in a solvent; the stirring speed of the dissolution is preferably 100 to 700 rpm, more preferably 150 to 650 rpm, and more preferably 200 to 450 rpm; the dissolution time is preferably 1 to 12 h, more preferably 2 to 10 h, and more preferably 5 to 8 h.
[0052] In the present invention, the mixing in step 2) is to drop the aromatic bromosilane solution into the first solution, and the rate of the dropping is 5 mL / s to 1 mL / s, preferably 4 mL / s to 2 mL / s, and more preferably 3 mL / s; the temperature of the substitution reaction in step 2) is 55 to 100°C, preferably 60 to 90°C, more preferably 65 to 85°C, and more preferably 70 to 80°C; the heating rate is 5 to 20°C / h, preferably 6 to 18°C / h, more preferably 8 to 15°C / h, and more preferably 10 to 13°C / h; the time is 1 to 24h, preferably 2 to 20h, more preferably 3 to 15h, and more preferably 5 to 10h.
[0053] In the present invention, the mixing temperature in step 2) is preferably room temperature; the stirring speed of the mixing is preferably 100 to 1600 rpm, more preferably 200 to 1200 rpm, and more preferably 300 to 500 rpm.
[0054] In the present invention, after the substitution reaction in step 2) is completed, it is preferred to further include centrifugal washing and drying operations.
[0055] In the present invention, the centrifugal washing is preferably placing the silane in a centrifuge tube for centrifugal treatment; the solid content of the centrifugal treatment is preferably 0.1-1 g / mL, more preferably 0.2-0.8 g / mL, more preferably 0.3-0.5 g / mL; the centrifugal rate of the centrifugal treatment is preferably 1000-10000 r / min, more preferably 1500-9500 r / min, more preferably 2000-7000 r / min; the centrifugal time of the centrifugal treatment is preferably 5-60 min, more preferably 10-50 min, more preferably 20-30 min; the number of centrifugal treatments is preferably 1-5 times, more preferably 2-4 times, more preferably 3 times.
[0056] In the present invention, the drying is preferably performed by placing the centrifuged silane in a vacuum oven for drying; the drying temperature is preferably 25 to 60° C., more preferably 30 to 55° C., and more preferably 35 to 40° C.; the drying time is preferably 1 to 48 h, more preferably 5 to 40 h, and more preferably 10 to 35 h; the drying power is preferably 100 to 500 W, more preferably 150 to 400 W, and more preferably 200 to 300 W.
[0057] In the present invention, the inorganic salt includes one or more of sodium carbonate, cesium carbonate, sodium bicarbonate, potassium carbonate, calcium carbonate, magnesium hydroxide and aluminum hydroxide; the alcohol in the alcohol solution of the inorganic salt includes one or more of ethanol, methanol, n-butanol, ethylene glycol, neopentyl alcohol, isopropanol and propanol; the solvent in the rosin solution and the solvent in the aromatic bromosilane solution independently include one or more of water, N,N-dimethylformamide, ethyl acetate, tetrahydrofuran, dimethyl sulfoxide, methanol, ethanol and propanol.
[0058] The present invention also provides a method for preparing a metasilicate composite powder, comprising the following steps:
[0059] S1: mixing the silane described in claim 1 with an organic solvent to obtain a second solution;
[0060] S2: mixing the second solution with the metasilicate slurry, reacting them to obtain a metasilicate composite powder.
[0061] In the present invention, the concentration of the second solution in S1 is 1-5 mol / L, preferably 2-4 mol / L, and more preferably 3 mol / L; the mixing temperature in S1 is 25-50°C, preferably 28-45°C, more preferably 30-42°C, and more preferably 35-40°C; the mixing time is 10-180 min, preferably 15-150 min, more preferably 20-120 min, and more preferably 30-80 min; the mixing speed is preferably 100-800 rpm, more preferably 200-700 rpm, and more preferably 300-500 rpm.
[0062] In the present invention, the mass molar ratio of metasilicate to silane in the metasilicate slurry in S2 is 1-20kg:1mol, preferably 3-15kg:1mol, further preferably 5-12kg:1mol, and more preferably 8-10kg:1mol; the concentration of the metasilicate slurry is 1-5kg / L, preferably 1.5-4kg / L, further preferably 2-3.5kg / L, and more preferably 2.5-3kg / L.
[0063] In the present invention, when the mass molar ratio of metasilicate to BMPMMP in the metasilicate slurry is higher than 20kg:1mol, the amount of BMPMMP added is too low, making it difficult to effectively modify and surface-modify the metasilicate, and thus it is difficult to effectively reduce the polarity of the metasilicate surface; and when the mass molar ratio of metasilicate to BMPMMP in the metasilicate slurry is lower than 1kg:1mol, BMPMMP is enriched on the surface of the metasilicate, and even most of the BMPMMP is adsorbed on the surface of the composite powder, and the metasilicate particles may be wrapped together, resulting in an increase in the particle size of some powders, which in turn leads to poor dispersion of the composite powder in the polyolefin elastomer matrix during processing due to poor wrapping effect.
[0064] In the present invention, the preparation step of the metasilicate slurry in S2 is preferably to add the dispersion into the metasilicate for stirring and infiltration; the stirring speed is preferably 500-2000rpm, more preferably 550-1500rpm, more preferably 650-1000rpm; the stirring time is preferably 1-12h, 2-10h, more preferably 5-8h; the stirring temperature is preferably 25-80°C, more preferably 30-60°C, more preferably 35-50°C.
[0065] In the present invention, the mixing in S2 is to spray the second solution into the metasilicate slurry, the rate of spraying the second solution into the metasilicate slurry is 1 to 30 mL / min, preferably 3 to 28 mL / min, more preferably 5 to 25 mL / min, more preferably 10 to 20 mL / min; the temperature is 25 to 45°C, preferably 28 to 42°C, more preferably 30 to 40°C, more preferably 32 to 38°C; the temperature of the reaction in S2 is 50 to 95°C, preferably 55 to 90°C, more preferably 60-85°C, more preferably 65-70°C; the heating rate is 5-30°C / h, preferably 10-25°C / h, more preferably 12-20°C / h, more preferably 15-18°C / h; the time is 0.2-6.0h, preferably 0.5-5.0h, more preferably 0.8-4.5h, more preferably 1.0-3.0h; the stirring rate of the reaction is preferably 1000-3000r / min, more preferably 1200-2500r / min, more preferably 1500-2000r / min.
[0066] In the present invention, the organic solvent comprises one or more of N,N-dimethylformamide, ethyl acetate, dimethyl sulfoxide and tetrahydrofuran; the median particle size D of the metasilicate in the metasilicate slurry is 50The particle size of the metasilicate is 1.0 to 4.0 μm, preferably 1.2 to 3.6 μm, further preferably 1.5 to 3.0 μm, and more preferably 2.0 to 2.5 μm; the dispersion in the metasilicate slurry includes one or more of methanol, ethylene glycol, ethanol, propanol, n-butanol, isopropanol, neopentyl alcohol, and isopropanol; the metasilicate includes natural calcic metasilicate.
[0067] In the present invention, after the reaction in S2 is completed, it is preferred that the steps of filtration, centrifugation, precipitation and drying are further performed.
[0068] In the present invention, the suction filtration is preferably to perform reduced pressure distillation on the metasilicate composite powder to remove the organic solvent, and add ethanol for suction filtration and washing; the pressure of the reduced pressure distillation is preferably -0.07 to -0.09 MPa, more preferably -0.08 MPa; the filter paper for the suction filtration and washing is preferably rapid filter paper; the number of layers of the rapid filter paper is preferably 1 to 3 layers, more preferably 2 layers; the number of times of the suction filtration and washing is preferably 1 to 5 times, more preferably 2 to 4 times, more preferably 3 times.
[0069] In the present invention, the centrifugation is preferably to place the filtered metasilicate composite powder in a centrifuge for centrifugal treatment; the solvent for the centrifugal treatment is preferably water; the solid content of the centrifugal treatment is preferably 1-30 mg / mL, more preferably 5-25 mg / mL, more preferably 10-20 mg / mL; the centrifugal treatment rate is preferably 1000-10000 r / min, more preferably 2000-8000 r / min, more preferably 3000-5000 r / min; the centrifugal treatment time is preferably 5-60 min, more preferably 10-50 min, more preferably 20-30 min.
[0070] In the present invention, the temperature of the precipitate is preferably 1-15°C, more preferably 2-12°C, and more preferably 5-10°C; the solid content of the precipitate is preferably 1-50 mg / mL, more preferably 5-45 mg / mL, and more preferably 10-25 mg / mL.
[0071] In the present invention, the drying is preferably flash drying; the drying temperature is preferably 90-160°C, more preferably 100-150°C, more preferably 120-130°C; the drying time is preferably 1-45 min, more preferably 5-40 min, more preferably 10-25 min.
[0072] The present invention also provides a metasilicate composite powder prepared by the above-mentioned metasilicate composite powder preparation method.
[0073] In the present invention, the median particle size (D50 ) is 1.0 to 4.0 μm, preferably 1.2 to 3.6 μm, more preferably 1.5 to 3.0 μm, and more preferably 2.0 to 2.5 μm; the metasilicate composite powder is a white powder.
[0074] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0075] Example 1
[0076] 1. Mix 212.25 g of safflower oil and methanol to obtain a safflower oil solution with a concentration of 2 mol / L, and disperse 210.0 g of sodium bicarbonate in ethanol to obtain a sodium bicarbonate dispersion with a concentration of 2.5 mol / L, and then add the safflower oil solution to the sodium bicarbonate dispersion at a drop rate of 3 mL / s, and then stir at a stirring rate of 1000 rpm for 6 hours at room temperature (25°C) to obtain a first solution;
[0077] 2. Dissolve 546.48 g of aromatic bromosilane and mix with propanol, stir at a stirring rate of 300 rpm for 8 hours to obtain an aromatic bromosilane solution with a concentration of 2 mol / L; then add the aromatic bromosilane solution to the first solution at a dropping rate of 3 mL / s at room temperature (25° C.) and a stirring rate of 1000 rpm, and then heat to 80° C. at a heating rate of 10° C. / h to carry out a substitution reaction for 10 hours. After the reaction is completed, place the product in a centrifuge tube, control the solid content to 0.5 g / mL, centrifuge at a centrifugal rate of 6000 r / min for 30 minutes, and place the product in a vacuum oven after three centrifugal treatments, and dry it at a temperature of 40° C. and a power of 300 W for 24 hours to obtain cloud fragrant base silane (BMPMMP);
[0078] 3. Mix 404.19 g of silane with a solution of N,N-dimethylformamide and ethyl acetate in a volume ratio of 1:1, control the mixing temperature to be 30°C, the stirring rate to be 400 rpm, and the mixing time to be 100 min to obtain a second solution with a concentration of 2 mol / L;
[0079] 4. Add ethanol to 10 kg of median particle size D 50The mixture was stirred and infiltrated in a natural calcium metasilicate (NMS) with a particle size of 1.6 μm, and the stirring rate was controlled to be 1000 rpm, the stirring time was 6 h, and the stirring temperature was 45 ° C to obtain a metasilicate slurry with a concentration of 2 kg / L; the second solution was then added to the metasilicate slurry in the form of a spray, wherein the spray rate was 15 mL / min, the spray temperature was 30 ° C, and then the temperature was increased to 75 ° C at a heating rate of 15 ° C / h, and the reaction was carried out at a stirring rate of 2000 r / min for 2.5 h, and then the product was heated at -0.0 The organic solvent was removed under a pressure of 9 MPa, and ethanol was added and filtered and washed repeatedly for 3 times, wherein the filter paper for filtration and washing was a 2-layer rapid filter paper; the product after filtration and washing was placed in a centrifuge, deionized water was added and the solid content was controlled to 20 mg / mL, the centrifugal speed was 6000 r / min, and the centrifugal treatment was performed for 30 minutes; then, it was precipitated at a temperature of 10°C and the solid content was controlled to 30 mg / mL, and finally dried at a temperature of 120°C for 25 minutes to obtain a metasilicate composite powder (BMPMMP-NMS).
[0080] After testing, the structural schematic diagram of the metasilicate composite powder BMPMMP-NMS obtained in this embodiment is as follows Figure 1 As shown, from Figure 1 It can be seen that a layer attached to the surface of the metasilicate composite powder obtained in this embodiment is a functional outer layer modified with BMPMMP, wherein the natural calcium sheet silicate is a microfiber with a certain aspect ratio, and BMPMMP is uniformly covered on the surface of the natural calcium metasilicate powder to form a better core-shell structure.
[0081] The particle size distribution diagram of the metasilicate composite powder obtained in this example is as follows: Figure 2 As shown, from Figure 2 It can be seen that the particle size distribution of the metasilicate composite powder prepared in this example is relatively uniform, presenting a single peak, and concentrated around 1.8 μm.
[0082] The SEM image of the metasilicate composite powder obtained in this example is as follows Figure 3 As shown, from Figure 3 It can be seen that there are flaky inclusions on the surface of the metasilicate composite powder obtained in this embodiment, and the flaky inclusions are relatively evenly dispersed on the surface of the metasilicate composite powder, and the overall modification effect is good.
[0083] Example 2
[0084] 1. Mix 212.25 g of safflower oil and ethanol to obtain a 1 mol / L safflower oil solution, and disperse 106.00 g of sodium carbonate in ethylene glycol to obtain a sodium carbonate dispersion with a concentration of 1 mol / L, and then add the safflower oil solution to the sodium carbonate dispersion at a drop rate of 1 mL / s, and then stir at a stirring rate of 1200 rpm for 1 hour at room temperature (25° C.) to obtain a first solution;
[0085] 2. Mix 273.24 g of aromatic bromosilane with propanol, stir for 12 h at a stirring rate of 100 rpm to obtain an aromatic bromosilane solution with a concentration of 1 mol / L; then add the aromatic bromosilane solution to the first solution at a dropping rate of 1 mL / s at room temperature (25 ° C) and a stirring rate of 1600 rpm, and then heat the mixture to 55 ° C at a heating rate of 5 ° C / h to carry out a substitution reaction for 1 h. After the reaction, place the product in a centrifuge tube, control the solid content to 0.1 g / mL, and centrifuge at a centrifugal rate of 1000 r / min for 60 min. After centrifugation once, place the product in a vacuum oven and dry it at a temperature of 25 ° C and a power of 100 W for 48 h to obtain cloud fragrant base silane (BMPMMP);
[0086] 3. Mix 404.19 g of silane with a solution of ethyl acetate and dimethyl sulfoxide in a volume ratio of 1:1, control the mixing temperature to be 25°C, the stirring rate to be 800 rpm, and the mixing time to be 10 min to obtain a second solution with a concentration of 1 mol / L;
[0087] 4. Add methanol to 1kg of median particle size D 50 The first step is to prepare a first molten silicate (NMS) having a particle size of 1.6 μm, and then stir and infiltrate the mixture, and control the stirring rate to be 500 rpm, the stirring time to be 12 h, and the stirring temperature to be 25 °C, to obtain a metasilicate slurry having a concentration of 1 kg / L; then the second solution is added to the metasilicate slurry in the form of a spray, wherein the spray rate is 1 mL / min, the spray temperature is 25 °C, and then the temperature is increased to 50 °C at a heating rate of 5 °C / h, and the mixture is reacted at a stirring rate of 3000 r / min for 6.0 h, and then the product is heated at -0. The organic solvent was removed under a pressure of 0.09MPa, and ethanol was added and filtered and washed repeatedly once, wherein the filter paper for filtration and washing was a 3-layer rapid filter paper; the product after filtration and washing was placed in a centrifuge, deionized water was added and the solid content was controlled to be 1 mg / mL, the centrifugal rate was 1000r / min, and the centrifugal treatment was performed for 60min; then it was precipitated at a temperature of 1°C and the solid content was controlled to be 1mg / mL, and finally dried at a temperature of 90°C for 45min to obtain a metasilicate composite powder (BMPMMP-NMS).
[0088] Example 3
[0089] 1. Mix 212.25 g of eugenol with ethanol to obtain a 3 mol / L eugenol solution, disperse 500.0 g of calcium carbonate in n-butanol to obtain a 5 mol / L calcium carbonate dispersion, then add the eugenol solution to the calcium carbonate dispersion at a drop rate of 5 mL / s, and then stir at a stirring rate of 100 rpm for 18 h at room temperature (25° C.) to obtain a first solution;
[0090] 2. Fully mix 819.72 g of aromatic bromosilane with ethyl acetate, stir at a stirring rate of 700 rpm for 1 h to obtain an aromatic bromosilane solution with a concentration of 3 mol / L; then, add the aromatic bromosilane solution to the first solution at a dropping rate of 5 mL / s at room temperature (25 ° C) and a stirring rate of 100 rpm, and then heat it to 100 ° C at a heating rate of 20 ° C / h, and carry out substitution reaction for 24 h. After the reaction, place the product in a centrifuge tube, control the solid content to 1 g / mL, and centrifuge at a centrifugal rate of 10000 r / min for 5 min. After centrifugation 5 times, place the product in a vacuum oven and dry it at a temperature of 60 ° C and a power of 500 W for 1 h to obtain cloud fragrant base silane (BMPMMP);
[0091] 3. Mix 404.19 g of silane with a solution of ethyl acetate and tetrahydrofuran in a volume ratio of 1:1, control the mixing temperature to be 50° C., the stirring rate to be 100 rpm, and the mixing time to be 180 min to obtain a second solution with a concentration of 5 mol / L;
[0092] 4. Add ethylene glycol to 20kg of median particle size D 50 The mixture was stirred and infiltrated in a natural calcic metasilicate (NMS) with a particle size of 1.6 μm, and the stirring rate was controlled to be 2000 rpm, the stirring time was 1 h, and the stirring temperature was 80 ° C to obtain a metasilicate slurry with a concentration of 5 kg / L; the second solution was then added to the metasilicate slurry in the form of a spray, wherein the spray rate was 30 mL / min, the spray temperature was 45 ° C, and then the temperature was increased to 95 ° C at a heating rate of 30 ° C / h, and the reaction was carried out at a stirring rate of 1000 r / min for 0.2 h, and then the product was heated at -0.0 The organic solvent was removed under a pressure of 9 MPa, and ethanol was added and filtered and washed repeatedly for 5 times, wherein the filter paper for filtration and washing was a single-layer rapid filter paper; the product after filtration and washing was placed in a centrifuge, deionized water was added and the solid content was controlled to 30 mg / mL, the centrifugal speed was 10000 r / min, and the centrifugal treatment was performed for 5 minutes; then, it was precipitated at a temperature of 15°C and the solid content was controlled to 50 mg / mL, and finally, it was dried at a temperature of 160°C for 1 minute to obtain a metasilicate composite powder (BMPMMP-NMS).
[0093] Comparative Example 1
[0094] The difference between this comparative example 1 and example 1 is that the amount of BMPMMP added in step 3 is 202.10 g; and the amount of natural calcium metasilicate (NMS) added in step 4 is 20 kg.
[0095] Comparative Example 2
[0096] The difference between this comparative example 2 and example 1 is that the amount of BMPMMP added in step 3 is 606.29 g; and the amount of natural calcium metasilicate (NMS) added in step 4 is 1 kg.
[0097] Experimental Example 1
[0098] The metasilicate composite powder (BMPMMP-NMS) prepared in Examples 1 to 3, the metasilicate composite powder (BMPMMP-NMS) prepared in Comparative Examples 1 to 2, and the natural calcium metasilicate (NMS) without any modification were tested for activation rate and oil absorption value. The test results are shown in Table 1:
[0099] Among them, activation rate: dry powder is tested by weighing method;
[0100] Oil absorption value: tested in accordance with DB / T5211.15-2014 standard.
[0101] Table 1 Activation rate and oil absorption value test results
[0102]
[0103] As can be seen from Table 1, through the test results of Examples 1 to 3 and the natural calcareous metasilicate (NMS) without any modification, it can be seen that the activation rate of the metasilicate composite powder BMPMMP-NMS after hybridization with BMPMMP increased significantly from the original 23.4% to 96.3%, indicating that BMPMMP can greatly improve the surface polarity of natural calcareous metasilicate. Moreover, the oil absorption value of the metasilicate composite powder also decreased significantly, indicating that the metasilicate composite powder modified by BMPMMP can effectively shield the surface hydroxyl groups of natural calcareous metasilicate, significantly reduce its polarity, and can greatly reduce the processing cost; Comparison From the test results of Examples 1 and 2, it can be seen that when the mass molar ratio of metasilicate to BMPMMP in the metasilicate slurry is higher than 20kg:1mol, that is, when the amount of BMPMMP added is too low, the final shielding effect is general, and the overall modification effect on the natural calcium metasilicate powder is poor; when the mass molar ratio of metasilicate to BMPMMP in the metasilicate slurry is lower than 1kg:1mol, that is, when the amount of BMPMMP added is too high, too much BMPMMP may wrap multiple natural calcium metasilicate particles together, so that the excess BMPMMP is adsorbed on the surface, which may fall off or peel off during processing, resulting in poor final modification effect. In summary, after adding BMPMMP, the activation rate and oil absorption value of the composite powder can be significantly improved, which is beneficial to the functional performance of the composite powder and the improvement of compatibility and dispersibility.
[0104] Experimental Example 2
[0105] The metasilicate composite powders (BMPMMP-NMS) prepared in Examples 1 to 3 and Comparative Examples 1 to 2 and natural calcium metasilicate (NMS) without any modification were added to the polyolefin elastomer, specifically, hydrogenated styrene-butadiene block copolymer SEBS (60 parts) and white oil (8 parts) were first mixed for 5 minutes, and then antioxidant 1010 and antioxidant 1076 (1 part) with a mass ratio of 1:1, lubricant silicone ester (1 part) and BMPMMP-NMS (or natural calcium metasilicate NMS without any modification) 40 parts were added in sequence, and mixed at a temperature of 170°C for 7 minutes to obtain 6 polyolefin elastomer composite material samples, and the mechanical properties, residual carbon rate and melt index of the 6 composite material samples were tested. The test results are shown in Table 2.
[0106] Among them, mechanical properties test: according to GB / T 528-2009, the butadiene rubber composite material is prepared into corresponding test specimens, and its tensile strength and elongation at break are tested.
[0107] Carbon residue rate test: In a nitrogen atmosphere, the temperature was increased at a rate of 10°C / min, and the ratio of the carbon residue mass to the initial mass was measured at 600°C.
[0108] Melt index test: According to the American ASTM D1238 standard, the test conditions are controlled at 190°C, the pressure is 2.16kg, and the test time is 10min.
[0109] Table 2 Mechanical and carbonization properties test results of composite samples
[0110]
[0111]
[0112] As can be seen from Table 2, by comparing the test results of the composite samples prepared from Examples 1 to 3 and natural calcareous metasilicate (NMS) without any modification, it can be seen that when the composite powder hybridized with BMPMMP is added to the polyolefin elastomer, the elongation at break of the polyolefin elastomer increases significantly, and the tensile strength is significantly improved, from 11.28 MPa to 24.75 MPa at the highest. Moreover, in terms of carbon residue at 600°C, the carbon residue rate of Examples 1 to 3 also increases significantly, from 14 wt% to about 31 wt%. At the same time, the melt index also increases significantly, indicating that the introduction of BMPMMP can effectively improve the surface properties of the natural calcareous metasilicate powder, making it more dispersible in the polyolefin elastomer, and significantly improving the mechanical properties of the composite material.
[0113] BMPMMP itself has a large conjugated aromatic ring, and as the heat rises, its carbonization can be significantly improved, which helps to improve the physical barrier properties in the combustion process, better exert the condensed phase barrier effect, and effectively inhibit the volatilization of smoke and combustible molecular chain fragments. In addition, the introduction of low-polarity BMPMMP can also significantly improve the processing fluidity of the composite material, which may be attributed to the reduction of the surface energy of natural calcium metasilicate, so that the composite powder can play a certain internal lubrication effect during the processing; however, when the mass molar ratio of metasilicate to BMPMMP in the metasilicate slurry is too high or too low (Comparative Examples 1-2), the mechanical properties of the polyolefin elastomer are generally improved, which may be due to the poor modification effect of BMPMMP on natural calcium metasilicate powder.
[0114] When the mass molar ratio of metasilicate to BMPMMP in the metasilicate slurry is too high, the surface energy decreases to a limited extent; when it is too low, multiple natural calcium metasilicate powders may be wrapped together, resulting in a passive increase in particle size, and the surface BMPMMP is easy to fall off during processing, and the dispersibility and compatibility are not effectively improved. At the same time, the carbonization of the polyolefin elastomer composite material is also limited. This may be because the surface BMPMMP and the natural calcium metasilicate cannot play a good synergistic carbonization role, and it is difficult to form a common force to promote carbonization. Not only that, the melt index also increases generally, indicating that when BMPMMP is too low or too high, the composite powder does not improve the processing fluidity of the polyolefin elastomer well, which is closely related to the poor dispersibility and compatibility caused by its surface energy. The above results show that the introduction of BMPMMP can improve the mechanical properties, carbonization and processing fluidity of the composite powder in the polyolefin elastomer, effectively improve the application value and application potential of the composite powder, and can also develop multi-functional powders suitable for polyolefin elastomers in a targeted manner.
[0115] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A silane, characterized in that The structural formula of the silane is shown in Formula I:
2. A method for preparing silane according to claim 1, characterized in that: The steps include: 1) mixing the safflower oil solution with the alcohol solution of the inorganic salt to obtain a first solution; 2) mixing the first solution with the aromatic bromosilane solution to carry out a substitution reaction to obtain aromatic silane; The structural formula of the caryophyllene in the caryophyllene solution is shown in Formula II: The structural formula of the aromatic bromosilane in the aromatic bromosilane solution is shown in Formula III:
3. The method for preparing a silane according to claim 2, characterized in that: The molar ratio of caryophyllene in the caryophyllene solution to the inorganic salt in the inorganic salt alcohol solution in step 1) is 1:1-5; The concentration of the eugenol solution is 1-3 mol / L; The concentration of the inorganic salt alcohol solution is 1 to 5 mol / L; The mixing in step 1) is to drop the phytamine solution into the alcohol solution of the inorganic salt, and the dropping rate is 5 mL / s to 1 mL / s.
4. The method for preparing silane according to any one of claims 1 to 3, characterized in that: The molar ratio of the aromatic bromosilane in the aromatic bromosilane solution to the caryophyllene in the caryophyllene solution in step 2) is 1 to 3:1; The concentration of the aromatic bromosilane solution is 1 to 3 mol / L; The mixing in step 2) is to drop the aromatic bromosilane solution into the first solution at a rate of 5 mL / s to 1 mL / s; The temperature of the substitution reaction in step 2) is 55-100° C., the heating rate is 5-20° C. / h, and the time is 1-24h.
5. The method for preparing silane according to claim 4, characterized in that: The inorganic salt in the alcohol solution of the inorganic salt includes one or more of sodium carbonate, cesium carbonate, sodium bicarbonate, potassium carbonate, calcium carbonate, magnesium hydroxide and aluminum hydroxide; The alcohol in the alcohol solution of the inorganic salt includes one or more of ethanol, methanol, n-butanol, ethylene glycol, neopentyl alcohol, isopropanol and propanol; The solvent in the carmine solution and the solvent in the aromatic bromosilane solution independently include one or more of water, N,N-dimethylformamide, ethyl acetate, tetrahydrofuran, dimethyl sulfoxide, methanol, ethanol and propanol.
6. A method for preparing a metasilicate composite powder, characterized in that: The steps include: S1: mixing the silane described in claim 1 with an organic solvent to obtain a second solution; S2: mixing the second solution with the metasilicate slurry, reacting them to obtain a metasilicate composite powder.
7. The method for preparing a metasilicate composite powder according to claim 6, characterized in that: The concentration of the second solution in S1 is 1 to 5 mol / L; The mixing temperature in S1 is 25 to 50° C. and the mixing time is 10 to 180 min.
8. The method for preparing a metasilicate composite powder according to claim 7, characterized in that: The mass molar ratio of the metasilicate to the silane in the metasilicate slurry in S2 is 1-20 kg:1 mol; The concentration of the metasilicate slurry is 1 to 5 kg / L; The mixing in S2 is spraying the second solution into the metasilicate slurry, wherein the rate of spraying the second solution into the metasilicate slurry is 1 to 30 mL / min and the temperature is 25 to 45° C.; The reaction temperature in S2 is 50-95°C, the heating rate is 5-30°C / h, and the reaction time is 0.2-6.0h.
9. The method for preparing a metasilicate composite powder according to any one of claims 6 to 8, characterized in that: The organic solvent includes one or more of N,N-dimethylformamide, ethyl acetate, dimethyl sulfoxide and tetrahydrofuran; The median particle size D of the metasilicate in the metasilicate slurry is 50 1.0~4.0μm; The dispersing liquid in the metasilicate slurry includes one or more of methanol, ethylene glycol, ethanol, propanol, n-butanol, isopropanol, neopentyl alcohol, and isopropanol; The metasilicate includes natural calcium metasilicate.
10. The metasilicate composite powder prepared by the method for preparing a metasilicate composite powder according to any one of claims 6 to 9.
Citation Information
Patent Citations
Silane and polyphenol co-modified inorganic mineral composite powder and preparation method thereof
CN117777761A
Organic electroluminescent materials and devices
CN118221716A
Yttrium containing metal complexes and olefin polymerization process
CN1216548A
Chemical compounds
GB8820218D0
Transition metal compound, catalyst for polymerizing olefins, and method for producing olefinic polymer
JP2001348389A